Oscillating meanings of the Nordic model: ideas and the welfare state in Finland and Sweden. Issue 4 (2nd October 2017) - Kuisma, Mikko
ABSTRACT: The future of the Nordic model of welfare has been widely debated in the academic literature. Some argue that the Nordic model is not sustainable under the conditions of globalization, while others argue that the way in which the Nordic model has produced long-term stability under uncertain structural conditions is evidence of the opposite. This article advances a different perspective through analyzing discourses and frameworks of meaning associated with the Nordic model, using Sweden and Finland as cases. Based on semi-structured elite interviews, I argue that while there is a consensus on the benefits of maintaining a Nordic model, the very ideas concerning the value foundations and institutional architecture of the model differ greatly between elites. There exists a variety of legitimate ideas associated with the Nordic model and, consequently, these approaches, all of which claim ownership of the term, represent legitimate facets of it, even when they initially would seem to contradict each other.